Role of booster vaccines and hybrid immunity against severe COVID-19 outcomes during BA.5 omicron predominance in Thailand - Kannikar Intawong; Suwat Chariyalertsak; Kittipan Chalom; Thanachol Wonghirundecha; Woravut Kowatcharakul; Aksara Thongprachum; Narain Chotirosniramit; Kajohnsak Noppakun; Krit Khwanngern; Worachet Teacharak; Prapon Piamanant; Pannawich Chantaklang; et al. (Taylor & Francis Group, 2023)
ABSTRACTOwing to both vaccine- and infection-induced immunity, the COVID-19 seroprevalence is ~90% in most countries. It is important to examine the protective role of booster vaccines and hybrid immunity in the COVID-endemic state. Utilizing a hospital information system for COVID-19, we conducted a cohort study by linking laboratory-confirmed COVID-19 case data to the national immunization records during the BA.5 omicron predominant period (1 August−31 December 2022) in Chiang Mai, Thailand. Out of 63,009 adults with COVID-19 included in the study, there were 125 (0.2%) severe COVID outcomes and 6.4% had a previous omicron infection. Protection against severe COVID-19 was highest among those with at least one booster vaccine (63%; aHR 0.37 [95%CI 0.19-0.73]) as compared to those without prior vaccination or natural infection. Hybrid immunity offered better protection (35%; aHR 0.65 [95%CI 0.09-4.73) than primary vaccine series alone or previous infection alone. Evaluating risk by age group, those aged 70 years or more had nearly 40 times (aHR 39.58 [95%CI 18.92-82.79]) the risk of severe-COVID-19 as compared to the 18-39-year age group. While booster vaccines remain the most effective way of protecting against severe COVID-19, particularly in the elderly, hybrid immunity may offer additional benefit.